Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Produk di PT Trimas Mitra Perkasa - Andi Putra; Heryenzus Heryenzus (Universitas Batanghari, 2022)
In the current era of business development, which is increasingly developing, it has an impact on brand image. Where the quality of the products produced can help consumers in making the right product purchase decisions. The purpose of this research is to test the influence of the quality of its products and its brand image on the decision to purchase its products at PT Trimas Mitra Perkasa. The consumers who are the population in this study are 150 consumers who have used and bought Lesso PPR and Rucika PVC at PT Trimas Mitra Perkasa. This research used a saturated sampling technique because the population was 150 respondents. Data collection was carried out by sharing the questionnaire online through a google form measured on a likert scale and then processed with the SPSS version 26 program. The analysis technique is multiple linear regression analysis. From the results of the T test, the quality of its products and its brand image positively influenced the purchasing decision of its products with the acquisition of T the calculation smaller than the t table of 6.157 > 1.976 and the acquisition of significance of 0.000 > α 0.05 and 5.893 > 1.976 and the significance of 0.000 > α 0.05. Simultaneously the quality of its products and its brand image influence its purchasing decisions.